Abnormal Amygdala Subregion Functional Connectivity in Patients with Crohn’s Disease with or without Anxiety and Depression - Jingwen Sun; Wei Sun; Kecen Yue; Yin Zhang; Xintong Wu; Wenjia Liu; Ling Zou; Haifeng Shi (Behavioural Neurology)
Objective. The aim of this study was to explore the resting-state functional connectivity (rsFC) of amygdala subregions in healthy controls (HCs) and in patients with Crohn’s disease (CD) both with and without anxiety or depression. Materials and Methods. A total of 33 patients with CD and with anxiety or depression (CDad group), 31 patients with CD but without anxiety or depression (CDnad group), and 29 age-, sex-, and education level-matched HCs underwent functional magnetic resonance imaging. rsFC analysis was used to analyze the FC between the amygdala subregions and other areas of the brain. Results. Compared with the HC group, the CDad group demonstrated decreased rsFC between the right laterobasal subregion and the left hippocampus (P<.001) and right middle frontal gyrus (P<.001) and between the left superficial subregion and the left insula (P<.001). Compared with the HC group, the CDnad group demonstrated decreased rsFC between the left centromedial subregion and the left insula (P<.001). Compared with the CDnad group, the CDad group demonstrated decreased rsFC between the left centromedial subregion and the right precuneus (P<.001) and postcentral gyrus (P<.001), between the right laterobasal subregion and the left hippocampus (P<.001), and between the left superficial subregion and the right middle frontal gyrus (P<.001). Conclusions. There are significant FC changes in the amygdala subregions in patients with CD. These changes may be related to the disease itself or to the symptoms of anxiety and depression.